Google Assistant In Teaching Pronunciation To Junior High School Students Post Pandemic Era - Muhammad Ihsan Sanusi; Muhammad Sofian Hadi (Jurnal Syntax Transformation, 2022)
The objective of this study is to teach pronunciation using Google Assistant to junior high school students. This study uses a quantitative approach with a pre-experimental design. In this study the researcher uses one class as the sample with a total of students are 25 students. The data were collected bteststest thatwase pre-test, treatment, and post-test. The research results are explained based on the research findings. the findings showed that the students’ results progress. the findingsreveals that Google Assistant is effective as one of media in teaching pronunciation to junior high school students